Nano COVID-19 Vaccines: the firsts RNA lipid nanoparticle vaccines being approved from history - Review (Research, Society and Development, 2020)
A new coronavirus, identified in Wuhan, China, has spread globally, infecting millions of people and causing significant morbidity and mortality. The pandemic state, declared by the World Health Organization on March 11, 2020, transformed the world and made people adapt to social distance to control the spread of the virus. The race against time in search of therapeutic solutions has become essential, and nanotechnology may be able to make vaccines available in record time to stimulate the immunization of individuals. Since the beginning of 2020, scientists and companies are rapidly advancing to make vaccine candidates available at a different rate compared to other pandemics that have existed. This review briefly presents the pros and cons of the third generation vaccines, Moderna / NIAID and Pfizer - BioNTech, which are in phase 3 tests, based on lipid RNA nanoparticles. Great collaborative efforts are being invested so that soon the world population will receive doses of vaccines with proven efficacy and enable increased survival, since the pandemic has already caused many irreversible losses.